198k views
0 votes
Generate a plan and describe the steps needed to solve the equation. 34 = –(m + 3)

2 Answers

4 votes

Answer:

Sample Response:

The negative sign outside the parentheses represents –1. Distribute the –1 to everything inside the parenthesis. Use the addition property of equality first to add 3 to both sides. Then use the division property of equality to divide both sides by -1.

User Denchr
by
5.4k points
4 votes

Answer:

m=−37

Explanation:

34 = -3 + -1m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add 'm' to each side of the equation.

34 + m = -3 + -1m + m

Combine like terms: -1m + m = 0

34 + m = -3 + 0

34 + m = -3

Add '-34' to each side of the equation.

34 + -34 + m = -3 + -34

Combine like terms: 34 + -34 = 0

0 + m = -3 + -34

m = -3 + -34

Combine like terms: -3 + -34 = -37

m = -37

User Itoun
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.